Effect of upper airway fat on tongue dilation during inspiration in awake people with obstructive sleep apnea. Issue 12 (29th July 2021) - Jugé, Lauriane; Olsza, Ida; Knapman, Fiona L; Burke, Peter G R; Brown, Elizabeth C; Stumbles, Emma; Bosquillon de Frescheville, Anne France; Gandevia, Simon C; Eckert, Danny J; Butler, Jane E; Bilston, Lynne E
Abstract: Study Objectives: To investigate the effect of upper airway fat composition on tongue inspiratory movement and obstructive sleep apnea (OSA). Methods: Participants without or with untreated OSA underwent a 3T magnetic resonance imaging (MRI) scan. Anatomical measurements were obtained from T2-weighted images. Mid-sagittal inspiratory tongue movements were imaged using tagged MRI during wakefulness. Tissue volumes and percentages of fat were quantified using an mDIXON scan. Results: Forty predominantly overweight participants with OSA were compared to 10 predominantly normal weight controls. After adjusting for age, BMI, and gender, the percentage of fat in the tongue was not different between groups (analysis of covariance [ANCOVA], p = 0.45), but apnoeic patients had a greater tongue volume (ANCOVA, p = 0.025). After adjusting for age, BMI, and gender, higher OSA severity was associated with larger whole tongue volume ( r = 0.51, p < 0.001), and greater dilatory motion of the anterior horizontal tongue compartment ( r = −0.33, p = 0.023), but not with upper airway fat percentage. Higher tongue fat percentage was associated with higher BMI and older age (Spearman r = 0.43, p = 0.002, and r =0.44, p = 0.001, respectively), but not with inspiratory tongue movements. Greater inspiratory tongue movement was associated with larger tongue volume (e.g. horizontal posterior compartment, r = −0.44, p = 0.002) and smaller nasopharyngeal airway (e.g. oblique compartment, r = 0.29, p = 0.040). Conclusions: Larger tongue volume and a smaller nasopharynx are associated with increased inspiratory tongue dilation during wakefulness in people with and without OSA. This compensatory response was not influenced by higher tongue fat content. Whether this is also true in more obese patient populations requires further investigation.